Ultrasound speckle noise reduction by radio-frequency data filtering - Santo, Verónica (2019)
Ultrasound is a commonly used imaging modality for the examination of several pathologies due to its non-invasiveness, affordability and easiness of use. However, ultrasound images are degraded by an intrinsic artefact called 'speckle', which is the result of the constructive and destructive coherent summation of the ultrasound echoes. This paper aims to generate B-mode images out of radio-frequency (RF) data following standard procedures, a series of steps such as envelope detection, log-compression and scan conversion. Some low pass filters will be applied to RF data in order to achieve B-mode images with high quality by speckle noise reduction.